2020
DOI: 10.13106/jafeb.2020.vol7.no6.233
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of CSR Associations on the Link between Brand Awareness and Purchase Intention

Abstract: This study uses the moderating model to explore the relationships between Corporate Social Responsibility (CSR) associations, brand awareness and consumer purchase intention. Besides investigating the direct effects of CSR associations on brand awareness and consumer purchase intention, this study also focuses on discovering the moderating role of CSR associations on the relationship between brand awareness and consumer purchase intention among Vietnamese students. Adapting scales from previous research, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…This study also proves that purchase intention can be increased through good perceived CSR. This finding is supported by several previous studies by Dang et al (2020;Hoang et al 2020;Cheng et al 2021;Gupta et al 2021). Alniacik et al (2020 found that the relationship between CSR and purchase intention can be strengthened by the presence of a personal value orientation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study also proves that purchase intention can be increased through good perceived CSR. This finding is supported by several previous studies by Dang et al (2020;Hoang et al 2020;Cheng et al 2021;Gupta et al 2021). Alniacik et al (2020 found that the relationship between CSR and purchase intention can be strengthened by the presence of a personal value orientation.…”
Section: Discussionsupporting
confidence: 91%
“…CSR can be interpreted as an agreement between the social environment and the company. However, it can also be understood as a social demand that must be faced by companies if they want to exist (Hoang et al, 2020). The benefits obtained from CSR activities are not only for the community, as companies also benefit from CSR, one of which is an increase in purchase intention from consumers (Dang et al, 2020;Hoang et al, 2020).…”
Section: Perceived Csr On Purchase Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in 2019, based on the MarkPlus survey, Shopee became the most embedded brand of e-commerce in Indonesian women's minds (Masitoh et al, 2019;www.industry.co.id, 2019). Products that have a high level of brand awareness will influence consumer purchasing decisions (Lee et al, 2019;Mashur et al, 2020;Hoang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%